The impact of labour market dynamics on the return-migration of immigrants - Govert E. Bijwaard; Christian Schluter; Jackline Wahba (Institute for the Study of Labor (IZA), 2011)
Using administrative panel data on the entire population of new labour immigrants to The Netherlands, we estimate the causal effects of labour dynamics on their return decisions. Specifically, the roles of unemployment and re-employment spells on immigration durations are examined. The endogeneity of labour market outcomes and the return migration decision, if ignored, confounds the causal effect. This empirical challenge is addressed using the timing-of-events method. We estimate the model separately for distinct immigrant groups, and find that, overall, unemployment spells shorten immigration durations, while re-employment spells delay returns for all but one group. The magnitude of the causal effect differs across groups.
urn:nbn:de:101:1-201106013361
Keywords: J61; J64; C41; 330; temporary migration; durations; timing of event method; labour market dynamics